Perancangan Sistem Absensi Driver Berbasis Aplikasi di PT. Permata Solusindo - Muhammad Yasir; Munandar; Reza Alif Anugrah; Thoyyibah Tanjung (CV. Multi Kreasi Media, 2023)
In the current era of globalization, technological progress is very rapid, especially in the field of technology. Where technological advances penetrate all social, economic and educational fields. The presence system in the company is very important to record the presence of drivers in the company. The mentoring system at PT. Permata Solusindo still uses manual attendance by entering it in the attendance book, so it is very easy to damage the driver assistance book paper. In this study, the methods of observation, interviews and literature study were used from several previous studies. To overcome the problems encountered, the author will provide alternative solutions to these problems by developing a support system that is currently operating by creating applications that can be downloaded or downloaded from the company's website, using this application provides convenience in the data search process and minimizes losses and errors of . when registering attendance data at PT.Permata Solusindo.